COVID-19 vaccine acceptance and hesitancy in Cameroon: a systematic review and meta-analysis - Cheuyem, Fabrice Zobel Lekeumo; Amani, Adidja; Nkodo, Iyawa Clarisse Alma; Boukeng, Lionel Bethold Keubou; Edzamba, Michel Franck; Nouko, Ariane; Guissana, Edwige Omona; Ngos, Christelle Sandrine; Achangwa, Chabeja; Mouangue, Christian (BMC public health, 2025)
The development of effective vaccines was a promising tool for ending the pandemic. However, the success of a vaccination programme hinges on achieving substantial community acceptance. In Cameroon, numerous studies have investigated the level of acceptance, hesitancy, and perception of COVID-19 vaccines, with mixed results. To provide a comprehensive understanding of these parameters, this meta-analysis aimed to estimate the pooled proportion of COVID-19 vaccine acceptance, hesitancy and perception in Cameroon. A systematic search of online databases, including PubMed, Google Scholar, and ScienceDirect, was conducted to identify relevant research articles. This study adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The extracted data were compiled in a Microsoft Excel spreadsheet and analyzed using R statistical software (version 4.3.3). The pooled proportion of COVID-19 vaccine acceptance, hesitancy, and perception was calculated using a random-effects meta-analysis. Funnel plots, Egger's, and Begg's tests were used to assess publication bias. Of the 1,346 records identified through the database search, 20 research articles were included in the systematic review and meta-analysis. The random-effects model showed that approximately 31.21% (95% CI: 23.49-38.94) of the participants was willing to accept the COVID-19 vaccine. More than two-thirds of the population (68.49%; 95% CI: 60.65-76.34) were vaccine hesitant. Half of the participants (51.81%; 95% CI: 42.70-60.93), had a negative perception of the COVID-19 vaccine. The acceptance rate progressed from the first semester of 2021 (27.21%; 95% CI: 10.38-44.05) to the first semester of 2022 (45.56%; 95% CI: 25.00-66.12). The pooled vaccine acceptance rate was 29.29% (95% CI: 19.86-38.72) for the general population and 39.24% (95% CI: 22.84-55.64) for healthcare workers. The pooled vaccine hesitancy rate was 70.39% (95% CI: 61.30-79.80) for the general population and 57.42% (95% CI: 4.05-71.80) for healthcare workers. Although progress in vaccine acceptance, targeted interventions remain necessary to address vaccine hesitancy in the country. Strategies such as enhancing access to accurate information, fostering trust in institutions, and strengthening community engagement remain crucial for increasing COVID-19 vaccine uptake.